Filtration Design Modeling Study with Variation in Number of Filters, Palm Oil Mill Effluent Meshing - Hajar Isworo; Muhammad Khalil; Ika Kusuma Nugraheni; Kurnia Dwi Artika (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
Processing activities of oil palm fruit into CPO produce liquid waste that can pollute the environment, so it is necessary to process liquid waste in palm oil mills. This study aims to design the filtration to overcome the existing pollution in the palm oil mill. The table shows the formation of 3 filter ABC formations has the highest speed of 6.419 m/s. When we place a large meshing hole on the first level, the speed and speed are smaller, this can be seen in the CBA, CBAC and CBACB formations. The meshing formation with a small size in the first position can increase the speed and pressure, we can see this in the ABC, ABCA and ABCAB formations so that the oil palm wastewater filtration process can run smoothly without a decrease in fluid velocity.